Ten species of liverworts and hornworts new to Guangxi, China - HUANG Ping1,2, TANG Qiming2, XIANG Youliang3, HO Boon-Chuan4, WANG Shunli2,3, WEI Yumei2* (Guangxi Zhiwu)
Based on the examination of specimens collected from Baise, Guilin, Hechi and Nanning regions of Guangxi from 2019 to 2022, ten species of liverworts and hornworts, including Riccia cavernosa Hoffm., R. nipponica S. Hatt., Metacalypogeia alternifolia(Nees)Grolle, Bazzania angustistipula N. Kitag., Cheilolejeunea kitagawae W. Ye & R.L. Zhu, Cololejeunea magnistyla(Horik.)Mizut., Colura calyptrifolia(Hook.)Dumort., Lejeunea convexiloba M.L. So & R.L. Zhu, Anthoceros angustus Steph., and A. subtilis Steph., are reported new to Guangxi. Among them, Colura calyptrifolia represents the first record for Chinese mainland, and Metacalypogeia is a new genus record for Guangxi. The diagnostic characters, voucher specimens, distribution, microscopic illustrations and taxonomic notes are also documented for each species. This study provides useful knowledge to better understand the bryophytes biodiversity in Guangxi, as well as in China.